Church and social conflicts in the Andes: The "ecclesiastical indigenism" - Vega-Centeno Bocángel, Imelda (2001)
In a previous work we have referred to "ecclesiastical indigenism" as the current of thought and pro-indigenous action inspired by evangelical values ​​of justice and solidarity, led by authorities or by representatives of the Church. With regard to this expression, some reader, turned interlocutor, has expressed discomfort or dissatisfaction with an attempt to "characterize" a certain rural pastoral care of bishops and priests at the beginning of the century. From the sociological point of view, we maintain that the temporal action expressed by the social pastoral of the Church of all times can be analyzed and measured in the same terms as any other social phenomenon.